Vaginal delivery through an intrapartum bucket handle cervical tear: a rare case report - Verma, Aruna; Pandey, Himani; Rana, Ravita; Parveen, Shazia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Cervical tears, though rare, pose serious risks to maternal health, especially postpartum haemorrhage. During labour, these injuries can include cervical avulsion, annular detachment, bucket-handle tears, and lateral tears. Our case report presents a rare instance of spontaneous vaginal birth through a posterior bucket-handle cervical tear in a primiparous woman. This occurred despite the external cervical os being partially dilated without known risk factors. This situation serves as a warning that strong uterine contractions accompanied by a failure of the external cervical os to dilate may indicate an imminent cervical tear. In cases of excessive postpartum blood loss, it is essential to maintain a high level of suspicion for cervical tears. This emphasizes the importance of thoroughly inspecting the genital canal after a vaginal birth. Prompt diagnosis, repair, anatomical restoration, and haemostasis are essential for achieving the best outcomes.